2011
DOI: 10.1097/aln.0b013e3182070c3a
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Activates Intestinal Sphingosine Kinase to Protect against Renal Ischemia–Reperfusion-induced Liver and Intestine Injury

Abstract: Background Renal ischemia–reperfusion injury (IRI) is a major cause of acute kidney injury and often leads to multi-organ dysfunction and systemic inflammation. Volatile anesthetics have potent antiinflammatory effects and we aimed to determine whether the representative volatile anesthetic isoflurane protects against acute kidney injury-induced liver and intestinal injury and the mechanisms involved in this protection. Methods Mice were anesthetized with pentobarbital and subjected to 30 min of left renal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 62 publications
4
33
0
Order By: Relevance
“…Both LPA and S1P can also be found in ovarian cancer ascites at 5-to 10-fold the typical plasma concentration, although the specific cell types responsible for this production are unknown 30,31 . Synthesis of LPs by neutrophils, mast cells, mononuclear cells, intestinal, lung, and uterine epithelium, testis, ovaries, and kidneys has also been reported 32-39 . It is likely the production by these, and other as yet unidentified cell types, is responsible for managing the recruitment of specific cells to sites in the microenvironment within certain tissue structures, or to stimulate growth in isolated areas, such as the LPA-mediated neurogenesis of post-mitotic cortical neurons 40 .…”
Section: Synthesis and Degradation Of Lpsmentioning
confidence: 88%
“…Both LPA and S1P can also be found in ovarian cancer ascites at 5-to 10-fold the typical plasma concentration, although the specific cell types responsible for this production are unknown 30,31 . Synthesis of LPs by neutrophils, mast cells, mononuclear cells, intestinal, lung, and uterine epithelium, testis, ovaries, and kidneys has also been reported 32-39 . It is likely the production by these, and other as yet unidentified cell types, is responsible for managing the recruitment of specific cells to sites in the microenvironment within certain tissue structures, or to stimulate growth in isolated areas, such as the LPA-mediated neurogenesis of post-mitotic cortical neurons 40 .…”
Section: Synthesis and Degradation Of Lpsmentioning
confidence: 88%
“…A growing body of evidence shows an organ protective effect against IRI in vivo by volatile anesthetics, such as isoflurane and xenon. 79,16 miRNAs are known to be involved in the development of IRI in several organs and in the protective effect of ischemic preconditioning. 25,26,29 Data obtained from cultured neuron-like cells suggest miR-203 might contribute to neuroprotection conferred by isoflurane preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Preconditioning induced by volatile anesthetics, such as isoflurane confers significant protection against renal IRI. 7,8 The noble gas xenon (Xe) has many properties of an ideal anesthetic. 912 A series of investigations has shown that xenon exhibits organoprotective properties against IRI in the heart, brain, and kidney.…”
mentioning
confidence: 99%
“…13 In situ labeling of fragmented DNA was performed with TUNEL stain (green fluorescence) using a commercially available in situ cell death detection kit (Roche, Indianapolis, IN) according to the instructions provided by the manufacturer. TUNEL-positive cells per high power field (hpf, 400X) were counted to quantify apoptosis.…”
Section: Methodsmentioning
confidence: 99%